Epigenetic regulation of transcriptional plasticity associated with developmental song learning - Kelly, Theresa K. (Proc Biol Sci, 2018)
Ethologists discovered over 100 years ago that some lifelong behavioural patterns were acquired exclusively during restricted developmental phases called critical periods (CPs). Developmental song learning in zebra finches is one of the most striking examples of a CP for complex learned behaviour. After post-hatch day 65, whether or not a juvenile male can memorize the song of a ‘tutor' depends on his experiences in the month prior. If he experienced a tutor, he can no longer learn, but if he has been isolated from hearing a tutor the learning period is extended. We aimed to identify how tutor experience alters the brain and controls the ability to learn. Epigenetic landscapes are modulated by experience and are able to regulate the transcription of sets of genes, thereby affecting cellular function. Thus, we hypothesized that tutor experiences determine the epigenetic landscape in the auditory forebrain, a region required for tutor song memorization. Using ChIPseq, RNAseq and molecular biology, we provide evidence that naturalistic experiences associated with the ability to learn can induce epigenetic changes, and propose transcriptional plasticity as a mediator of CP learning potential.